Developing criteria and indicators of community managed forests as assessment and learning tools: objectives, methodologies and results - Burford de Oliveira, N.; McDougall, C.; Ritchie, B.; Hartanto, H.; Haggith, M.; Setyawati, T. (Center for International Forestry Research, 2000)
This report explores criteria and indicators (C&I) for monitoring and assessing the sustainability of community managed forests (CMFs), and offers some insights into methodological tools and conceptual approaches for C&I development. The research was intended to explore the potential value of C&I to forest communities, their partners and their representative organisations to legitimise and enhance management, including strengthening of control over forest resources and facilitating the equitable distribution of the costs and benefits of forest management. The C&I for CMF tests involved six forest communities and their partners in Central Province, Cameroon, the Amazonian state of Pará, Brazil, and West Kalimantan, Indonesia. Each test was of approximately one-month duration. The core teams included an ecologist, a social scientist and a forest management specialist. Local involvement was an essential element of the research process. Facilitators enabled the active participation of community members in the critical appraisal of the C&I. After each field test, academics, policy makers, representatives of local and national non-governmental organisations, and representatives of other forest communities reviewed the emergent 'draft' C&I. Over 750 statements of principles, criteria, indicators and verifiers were generated by the tests. There is an evaluation of C&I testing processes and C&I for CMF development methodologies, as well as an analysis of the C&I for CMF. The comprehensive coverage of issues related to the sustainability of CMFs makes this report a valuable reference for those interested in implementing C&I for CMF, and for other users and purposes. These may include: researchers or policy makers analysing intersectoral impacts on CMFs; practitioners assessing and developing collaborative CMF initiatives; development planners and project managers evaluating or planning initiatives; and professors seeking guidance on incorporating community forestry into curricula for rural development, forestry and anthropology students.